Comparative analysis of cutting efficiency and surface maintenance between different types of implant drills: An in vitro study - Hochscheidt, Celso João; Shimizu, Roberto Hideo [UNESP]; Andrighetto, Augusto Ricardo; Pierezan, Rodrigo; Thomé, Geninho; Salatti, Rafael (Wolters Kluwer, 2017)
Introduction: This study evaluated cutting efficiency (CE) and linear wear of dental implant drills after 450 standardized osteotomies on bovine ribs. Diamond-like carbon-coated steel drills (SG), acid-treated steel drills (EG), and ceramic drills (ZG) were divided into 6 subgroups according to the number of uses. Materials and Methods: A robot-controlled program performed systematic instrumentation, timing, axial loading, and managed feed rate. CE was recorded in a polyurethane resin blank and end wear (VBBmax) was analyzed under stereo microscopy. Results: After osteotomies in beef ribs, CE for the Ø2.0-mm drill decreased 10.2% in SG and 10.9% in ZG; for the Ø3.0-mm drill, CE decreased 30.6% in SG, 8.5% in ZG, and improved in EG. The greatest wear occurred in Ø2.0-mm drills; ZG drills (Ø3.0 mm) exhibited only edge frittering, as confirmed on scanning electron microscopy. Conclusion: After 50 exposures to mechanical loads, steel and ceramic drills lost CE. Whereas cutting and thermal performance improved in experimental drills, the Ø2.0-mm drill exhibited the most signs of wear proportional to use. These findings suggest that, with the methodology employed, the life of these drills exceeds 50 osteotomies.
Keywords: Dental implants; Osteotomy; Performance testing; Tribology